PENGARUH MODEL PROJECT BASED LEARNING (PjBL) TERHADAP HASIL BELAJAR PENDIDIKAN PANCASILA SISWA KELAS II SDN 21 LUBUK LINTAH - Melani Risma, Aura; Tuljanah, Rahmia; Hendriani, Maifit (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the low learning outcomes of Pancasila Education among second-grade students at SDN 21 Lubuk Lintah. This study aimed to determine the effect of the Project Based Learning (PjBL) model on the learning outcomes of Pancasila Education among second-grade students at SDN 21 Lubuk Lintah. This study employed a quantitative approach using a quasi-experimental design with a Posttest Only Control Group Design. The population consisted of all second-grade students at SDN 21 Lubuk Lintah. The sample was selected using probability sampling with cluster random sampling, resulting in class II.2 as the experimental group and class II.3 as the control group, with 22 students in each class. The research instrument was a multiple-choice learning outcome test that had been tested for validity, reliability, item discrimination, and difficulty level. Data were analyzed using descriptive statistics, normality and homogeneity tests, and an Independent Sample t-test. The results showed that the mean posttest score of the experimental group was 84.09, while that of the control group was 73.41. The hypothesis test yielded a t-value of 3.461, which was greater than the t-table value of 2.02, with a significance value of 0.001 < 0.05. Therefore, H₀ was rejected and H₁ was accepted. It can be concluded that the Project Based Learning (PjBL) model had a significant effect on the learning outcomes of Pancasila Education among second-grade students at SDN 21 Lubuk Lintah.